Montréal... l'histoire oubliée (Histoire Québec, 1996)
Keywords: Arts sacrés; Leduc, Ozias; Musées; Peinture; Églises

Du projet de reconquête économique à l'idée de management: un bilan des études consacrées au mouvement Desjardins - Rousseau, Yvan (Histoire sociale / Social History, 1996)
Keywords: Banques; Caisses populaires

Banque Canadienne Nationale: cent ans d'histoire (s.é., 1974)
Keywords: Banque Canadienne Nationale; Banque d'Hochelaga; Banques

La première banque au Canada. Histoire de la Banque de Montréal - Denison, Merrill (McClelland and Stewart, 1966)
Keywords: Banque de Montréal; Banques

Du tableau noir à l'électronique: l'histoire de la Bourse de Montréal / Chalk to Computers: The Story of the Montreal Stock Exchange - Collard, Edgar Andrew (s.é., 1974)
Keywords: Bourse

100 ans d'histoire: revue de l'exercice 1991 - Association des banquiers canadiens (Association des banquiers canadiens, 1991)
Keywords: Banques

L'arme favorite de l'épicier indépendant: éléments d'une histoire sociale du crédit (Montréal, 1920-1940) - Taschereau, Sylvie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
Keywords: Épicerie

Recherches sur l'histoire des banques dans le Bas-Canada de la cession à la rébellion des patriotes en 1837 - Levasseur, Edgar (Université Laval, 1952)
Keywords: Banques

Division sexuelle du travail en milieu bancaire: Montréal, 1900-1930 - Dagenais, Michèle (Université du Québec à Montréal, 1987)
Keywords: Banques; Femmes; Travail

Le crédit dans une caisse populaire en milieu urbain: Saint-Alphonse d'Youville, 1940-1950 - Poirier, Jean (Université du Québec à Montréal, 1991)
Keywords: Banques; Caisses populaires; Saint-Alphonse-d'Youville (paroisse)

La Banque du Peuple, 1835-1871, and its Failure, 1895 - Greenfield, Robert S. (Université McGill, 1968)
Keywords: Banque du Peuple; Banques

Insuring against every man : an economic and social history of the Guarantee Company of North America, 1871-1919 - Doyon, Charles (Université McGill, 1980)
Keywords: Fiducie; Guarantee Trust Company

La fabrication des timbres-poste canadiens et des billets de banque à Montréal de 1871 à 1889: la British American Bank Note - Caron, Normand (Histoire Québec, 1996)
Keywords: Banques; Imprimerie; Poste

L'encadrement de la maternité au Québec entre les deux guerres: les gardes de La Métropolitaine, les Gouttes de lait et l'Assistance maternelle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1990)
Keywords: Assistance maternelle; Assurance; Enfants; Femmes; Goutte de lait; Infirmières; La Métropolitaine

Prêtres et prêteurs au XIXe siècle - Hudon, Christine (Histoire sociale / Social History, 1993)

FLEMING, JOHN - Deslauriers, Peter (Dictionnaire biographique du Canada, 1987)

La gestion des opérations financières du gouvernement québécois, 1867-1920 - Vallières, Marc (Université Laval, 1980)
Keywords: Fiscalité

L'assurance-vie Desjardins, 1948-1968 - Laville, Christian (Université Laval, 1971)
Keywords: Assurance; Banques; Caisses populaires

Desjardins et les Caisses Populaires 1900-1920, naissance et développement d'un mouvement coopératif - Poulin, Pierre (Université Laval, 1991)
Keywords: Banques; Caisses populaires; Desjardins, Alphonse

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Par l'ordre et par l'économie. Les Caisses d'épargne et l'État au Québec (1819-1871) - Vanasse, Frédéric (Université du Québec à Montréal, 1991)
Keywords: Banques

La première caisse populaire de Montréal fut fondée par des leaders du mouvement ouvrier - Bélanger, Guy (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1998)
Keywords: Caisses populaires; Desjardins, Alphonse

Les Capitaux français et le Québec, 1855-1900 - Quinn, Majella (Université Laval, 1968)

The Origins and Early History of the Montreal City and District Savings Bank 1846-1871 - Cooper, John Irwin (Canadian Catholic Historical Association Report, 1945)
Keywords: Banque d'épargne de la cité et du district de Montréal; Banques

Historical Sketch of the Molson Bank - Hopkins, J. Castel (Canadian Annual Review, 1910)
Keywords: Banque Molson; Banques

The Centenary of the Bank of Montreal, 1817-1917 (Bank of Montreal, 1917)
Keywords: Banque de Montréal; Banques

Historical Sketch of the Bank of Montreal - Hopkins, J. Castel (Canadian Annual Review, 1910)
Keywords: Banque de Montréal; Banques

Some Early Canadian Savings Banks - Cooper, John Irwin (Canadian Paper Money Journal, 1981)
Keywords: Banques

Joseph Masson, dernier seigneur de Terrebonne, 1791-1847 - Masson, Henri (Henri Masson, 1972)
Keywords: Marchands; Masson, Joseph

The Century of the Sun; the First Hundred Years of Sun Life Assurance Company of Canada - Schull, Joseph (Macmillan of Canada, 1971)
Keywords: Assurance; Sun Life Assurance

Un Astre centenaire. Les cent premières années de Sun Life du Canada compagnie d'assurance-vie - Schull, Joseph (Presses de l'Université Laval, 1971)
Keywords: Assurance; Sun Life Assurance

The First Hundred Years: History of the Montreal City and District Savings Bank, 1846-1946 - Smyth, T. Taggart (s.é., 1946)
Keywords: Banque d'épargne de la cité et du district de Montréal; Banques

Banking en français: les banques canadiennes-françaises de 1835 à 1925 - Rudin, Ronald (Boréal, 1988)
Keywords: Banque Canadienne Nationale; Banque Jacques-Cartier; Banque Ville-Marie; Banque d'Hochelaga; Banque du Peuple; Banques

Montreal Banks and the Urban Development of Quebec, 1840-1914 - Rudin, Ronald (Shaping the Urban Landscape. Aspects of the Canadian City-Building Process, 1982)
Keywords: Banques

The Sun Life Insurance Company of Montreal, 1872-1900 - Pollack, Gladys (Université McGill, 1980)
Keywords: Assurance; Sun Life Assurance

Banking en français: The French Banks of Quebec, 1835-1925 - Rudin, Ronald (University of Toronto Press, 1985)
Keywords: Banque Canadienne Nationale; Banque Jacques-Cartier; Banque Ville-Marie; Banque d'Hochelaga; Banque du Peuple; Banques

Fiftieth Anniversary of the Royal Bank of Canada, Established October Eighteenth MDCCCLXIX, a Record of its Progress During the Past Half Century, 1869-1919 - Royal Bank Of Canada (s.é., 1919)
Keywords: Banque Royale; Banques

Growing with Canada! The Story of Canada's Oldest and Youngest Stock Exchanges - Norman, Henry G. (Newcomen Society in North America, 1957)
Keywords: Bourse

The President's Book; the Story of the Sun Life Assurance Company of Canada - Harris, George Henry (Sun Life Assurance, 1928)
Keywords: Assurance; Sun Life Assurance

First in the Field - Phoenix Assurance Company Limited Of London (s.é., 1954)
Keywords: Assurance; Phoenix Assurance

History and Organisation of the Montreal Stock Exchange - Johnson, J. S. (Université McGill, 1934)
Keywords: Bourse

La Caisse populaire Notre-Dame de la Merci de Montréal: à tire d'ailes. Une ascension continue depuis 25 ans: album souvenir, 1960-1985 - Lafortune, Hélène; Robert, Normand (Archiv-histo, 1985)
Keywords: Banques; Caisses populaires; Notre-Dame-de-la-Merci (paroisse)

Un pionnier de l'économie au Québec: Joseph Versailles (1881-1931), le fondateur de Montréal-Est - Fournier, Oliva (Éditions de la libellule, 1974)
Keywords: Montréal-Est; Versailles, Joseph

Historique de l'Union régionale de Montréal des caisses populaires Desjardins - Girardin, Émile (s.é., 1974)
Keywords: Banques; Caisses populaires

La finance - Favreau, Lucien; Charbonneau, Roger (Montréal économique, 1943)

Nos fondateurs. La Sauvegarde, 1903-1953 - Ducharme, J. Oscar; Denis, Raymond (La Sauvegarde, 1953)
Keywords: Assurance; La Sauvegarde

A Very Human Story: A Brief History of the Royal Trust Company, Its First 75 Years - Collard, Edgar Andrew (Royal Trust Co., 1975)
Keywords: Fiducie; Royal Trust Company

Caisse populaire de St-Jean Vianney: 35e anniversaire, 1946-1981 (La Caisse, 1981)
Keywords: Banques; Caisses populaires; Saint-Jean Vianney (paroisse)

Cinquante années de progrès 1876-1926 (Société des artisans canadiens-français, 1926)
Keywords: Assurance; Société des artisans canadiens-français

La Caisse populaire de Saint-Stanislas, 1936-1986: 50 ans de service (Éditions Souvenance, 1986)
Keywords: Banques; Caisses populaires; Saint-Stanislas (paroisse)

Spatio-dynamique bancaire en milieu urbanisé: l'île de Montréal (1945-1972) - Boisvert, Michel (Revue de Géographie de Montréal, 1975)
Keywords: Banques

Le système financier montréalais: quelques lacunes - Briant, Peter; Whittaker, Gary (L'Actualité économique, 1974)

Un financier qui fut un "diable d'homme" - Macmillan, David S. (Le banquier et revue IBC, 1978)
Keywords: Dunlop, James

La bourse de Montréal sous le régime français - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1915)

Notre milieu: Montréal économique VIII. La finance - Favreau, Lucien; Charbonneau, Roger (L'Actualité économique, 1943)
Keywords: Banques

Montréal, métropole financière - Dell'Aniello, Paul (L'Actualité économique, 1967)
Keywords: Banques; Métropole

The Bank of Montreal Issues since 1871 - Allen, Harold D. (Canadian Paper Money Journal, 1969)
Keywords: Banque de Montréal; Banques

La bourse de Montréal au début du siècle - Francoeur, (Madame) (Assurances, 1983)
Keywords: Bourse

L'évolution de la bourse de Montréal depuis un demi-siècle - Lortie, Pierre (Assurances, 1982)
Keywords: Bourse

The Bank of Montreal: from Survival to Success - Skidmore, P. G. (Bulletin of Canadian Studies, 1983)
Keywords: Banque de Montréal; Banques

Toronto vs. Montreal: The Struggle for Financial Hegemony, 1860-1875 - Masters, D. C. (Canadian Historical Review, 1941)
Keywords: Banques; Métropole

Canada's First Bank: A History of the Bank of Montreal - Denison, Merrill (McClelland and Stewart, 1966)
Keywords: Banque de Montréal; Banques

A Bank Merger unlike the Others: The Establishment of the Banque Canadienne Nationale - Rudin, Ronald (Canadian Historical Review, 1980)
Keywords: Banque Canadienne Nationale; Banque d'Hochelaga; Banques

Historical Sketch of the Sun Life Assurance Company of Canada - Hopkins, J. Castel (Canadian Annual Review, 1910)
Keywords: Assurance; Sun Life Assurance

Bankers' Hours: Life Behind the Wicket at the Banque d'Hochelaga, 1901-21 - Rudin, Ronald (Labour / Le travailleur, 1986)
Keywords: Banque d'Hochelaga; Banques

Itinéraires professionnels masculins et féminins en milieu bancaire: le cas de la Banque d'Hochelaga, 1900-1929 - Dagenais, Michèle (Labour / Le travail, 1989)
Keywords: Banque d'Hochelaga; Banques; Femmes; Travail

Some Early Canadian Savings Banks - Cooper, John Irwin (Canadian Banker, 1950)
Keywords: Banques

Banking on Quebec: the French Banks and the Mobilization of French Funds, 1835-1925 - Rudin, Ronald (Journal of Canadian Studies / Revue d'études canadiennes, 1985)
Keywords: Banques

Le secteur financier et le développement économique du Québec - Ryba, André (L'Actualité économique, 1974)